What explains the link between romantic conflict with gambling problems? Testing a serial mediational model - Hagen, Amanda E. F.; Nogueira-Arjona, Raquel; Sherry, Simon B.; Rodriguez, Lindsey M.; Yakovenko, Igor; Stewart, Sherry H. (Frontiers in Psychology, 2023)
Introduction While individuals have many motives to gamble, one particularly risky motive for gambling is to cope with negative affect. Conflict with one’s romantic partner is a strong predictor of negative affect, which may elicit coping motives for gambling and, in turn, gambling-related problems. Support for this mediational model was demonstrated in relation to drinking-related problems. We extended this model to gambling. Method Using a cross-sectional design, we examined links between romantic conflict (Partner-Specific Rejecting Behaviors Scale), negative affect (Depression, Anxiety, and Stress Scales-21), coping gambling motives (Gambling Motives Questionnaire, coping subscale), and gambling-related problems [Problem Gambling Severity Index (PGSI)] in 206 regular gamblers (64% men; mean age = 44.7 years; mean PGSI = 8.7) who were in a romantic relationship and recruited through Qualtrics Panels in July 2021. Results Results supported our hypothesis that the model would explain a significant amount of variance in gambling-related problems, β = 0.35, 95% CI [0.24, 0.47], and that the association between romantic conflict and gambling-related problems would be sequentially mediated through negative affect and coping gambling motives, β = 0.07, 95% CI [0.03, 0.11], and also showed a strong single mediation pathway through negative affect alone, β = 0.24, 95% CI [0.16, 0.35]. Discussion Negative affect and coping gambling motives partially explain the link between romantic conflict and gambling-related problems. Interventions should target both negative affect and coping gambling motives in response to romantic conflict to reduce gambling-related problems in partnered gamblers.